Eozinofilni gastroenteritis - Štabuc, Borut (Zdravniški vestnik, 2003)
Background. Eosinophilic gastroenteritis (EGE) is a rare disorder of unknown etiology, characterised by infiltrating eosinophils into one or more layers ofgastrointestinal tract and various gastrointestinal manifestations. Signs and symptoms are related to the layer and extent of bowel involved with eosinophilic infiltration bowel with mucosa, muscle, subserosa or all three affected. Steroid therapy remains the corner stone of treatment. Patients and methods. This paper describes a case of 70 year old male patient with eosinophilic mucosal disease of upper intestinal wall repeatedly admitted because of epigastralgias, nausea, vomiting and losing weight. Because of hypereosinophilia, a biopsy of duodenal mucosa was performed, despite the normal endoscopic appearance. Numerous eosinophilic infiltrates were histologically confirmed in mucosa and submucosa and remission followed metilprednisolon therapy. Results. After two years signs of ilness reapearred,and again metilprednisolon therapy was followed by remission which still last. Conclusions. EGE needs to be recognized by the clinician because it can masquerade as the irritable bowel syndrome. Thie diagnosis of EGE is confirmed by a characteristic biopsy. Treatment is empiric and gauged to the severity of the clinical manifestations.
Keywords: Aged; Diagnosis; Drug Therapy; Eosinophilia; Eozinofilija; Gastroenteritis; Helicobacter Pylori; Methylprednisolone; Metilprednizolon; Pathology; prebavila; Starostniki